Functional responses of key marine bacteria to environmental change – toward genetic counselling for coastal waters - Pinhassi, Jarone; Farnelid, Hanna; García, Sandra Martínez; Teira, Eva; Galand, Pierre E.; Obernosterer, Ingrid; Quince, Christopher; Vila-Costa, Maria; Gasol, Josep M.; Lundin, Daniel; Andersson, Anders F.; Labrenz, Matthias; et al. (Frontiers in Microbiology, 2022)
Coastal ecosystems deteriorate globally due to human-induced stress factors, like nutrient loading and pollution. Bacteria are critical to marine ecosystems, e.g. by regulating nutrient cycles, synthesizing vitamins, or degrading pollutants, thereby providing essential ecosystem services ultimately affecting economic activities. Yet, until now bacteria are overlooked both as mediators and indicators of ecosystem health, mainly due to methodological limitations in assessing bacterial ecosystem functions. However, these limitations are largely overcome by the advances in molecular biology and bioinformatics methods for characterizing the genetics that underlie functional traits of key bacterial populations – “key” in providing important ecosystem services, being abundant or by possessing high metabolic rates. It is therefore timely to analyse and define the functional responses of bacteria to human-induced effects on coastal ecosystem health. We posit that categorizing the responses of key marine bacterial populations to changes in environmental conditions through modern microbial oceanography methods will allow establishing the nascent field of genetic counselling for our coastal waters. This requires systematic field studies of linkages between functional traits of key bacterial populations and their ecosystem functions in coastal seas, complemented with systematic experimental analyses of the responses to different stressors. Research and training in environmental management along with dissemination of results and dialogue with societal actors are equally important to ensure the role of bacteria is understood as fundamentally important for coastal ecosystems. Using the responses of microorganisms as a tool to develop genetic counselling for coastal ecosystems can ultimately allow for integrating bacteria as indicators of environmental change.